Girls' cortisol concentrations, mothers' anxiety, and self- versus parent-ratings of autistic girls' anxiety. (March 2021) - Bitsika, Vicki; Sharpley, Christopher F.; Mandy, Will; McMillan, Mary E.; Agnew, Linda L.
Highlights: Assessment of anxiety in autistic girls is subject to various confounds. Mothers' own anxiety influenced their ratings of their autistic daughters' anxiety. Adolescent daughters' self-ratings of anxiety were most valid. Some autistic girls may disguise their anxiety. Abstract: Background: Autistic girls' change in salivary cortisol concentrations from morning to afternoon were compared with their parents' own anxiety states as potential correlates of the autistic girls' self-ratings of their anxiety and those given by their parents about their daughters' anxiety. Methods: Thirty-three autistic girls (6 yr to 10 yr, M  = 8.21 yr, SD = 1.29 yr) and 19 autistic adolescent females (11 yr to 15 yr, M  = 12.74 yr, SD = 1.52 yr) completed anxiety inventories about themselves and provided saliva samples in the morning and afternoon. Their mothers also rated their daughters' anxiety and their own anxiety. Results: There were no significant differences between mothers' and daughters' ratings of the latter's GAD. The autistic girls' self-ratings of their anxiety were more strongly influenced by their mothers' anxiety in the younger girls, but more responsive to their own chronic stress state (i.e., cortisol) in the adolescent girls. Conclusions: Mothers' evaluations of their autistic daughters' anxiety appear to be strongly influenced by their own anxiety. There was also some indication that autistic girls may disguise their anxiety.